Evidence‐based medicine meets person‐centred care: a collaborative perspective on the relationship. Issue 6 (10th September 2015) - Price, Amy I.; Djulbegovic, Ben; Biswas, Rakesh; Chatterjee, Pranab
Abstract: In a recent list‐serve, the way forward for evidence‐based medicine was discussed. The purpose of this paper was to share the reflections and multiple perspectives discussed in this peer‐to‐peer encounter and to invite the reader to think with a mind for positive change in the practice of health care. Let us begin with a simple question. What if we dared to look at evidence‐based medicine (EBM) and informed shared decision making like two wheels on a bike? They both need to be full of substance, well connected, lubricated and working in balance, propelled and guided by a competent driver, with good vision to get the bike where we want it to go. We need all the tools in the toolkit for the bike to stay operational and to meet the needs of the driver. By the same rationale, evidence alone is necessary but not sufficient for decision making; values are necessary and if neglected, may default to feelings based on social pressures and peer influence. Medical decisions, even shared ones, lack focus without evidence and application. Just as a bike may need a tune up from time to time to maintain optimal performance, EBM may benefit from a tune up where we challenge ourselves to move away from general assumptions and traditions and instead think clearly about the issues we face and how to ask well‐formed, specific questions to get the answers to meet the needs we face in health care.